Comparative effects of nebivolol and carvedilol on left ventricular diastolic function in older patients with heart failure and preserved ejection fraction - Kyungil Park; Tae-Ho Park (International Journal of Cardiology. Cardiovascular Risk and Prevention, 2023)
Background: Although many studies have compared carvedilol and nebivolol in heart failure (HF) patients with reduced left ventricular ejection fraction (LVEF), such comparative studies for the elderly have not been reported yet. Nebivolol is known to be effective for improving diastolic function of elderly patients with HF. Thus, this study aimed to determine whether nebivolol could improve LV diastolic function to a greater extent than carvedilol in older patients aged over 70 years. Methods: This trial was a prospective, randomized, open-label, single-center, active-controlled study that enrolled 62 patients with class II or III HF over 70 years of age with an LVEF ≥40%. Patients were randomized into a carvedilol group or a nebivolol group. Transthoracic echocardiography was performed at baseline and 12 months by the same investigator who was blinded to clinical data. The primary endpoint was E/e′ measured by echocardiographic evaluation 12 months after treatment. Results: The median duration of follow-up was 24 months. Baseline clinical characteristics and echocardiographic parameters, such as LV diastolic function indices, did not differ significantly between carvedilol and nebivolol groups. Twelve-month follow-up echocardiography data showed no significant difference in E/e′ or other LV diastolic function indices between the two groups. There were no significant changes in echocardiographic parameters over 12 months in either group. Conclusions: There was no difference between carvedilol and nebivolol for improving diastolic function of elderly HF patients with LVEF ≥40%. This study showed no superiority of nebivolol over carvedilol in elderly patients with HF.